Robot-Assisted Surgery of an Iliac Artery Aneurysm: A Case Report. Issue 6 (November 2022) - Hoffmann, Grischa; Rusch, Melanie; Berndt, Rouven; Beckmann, Jan; Becker, Thomas; Cremer, Jochen; Rusch, Rene
Robot-assisted surgery has not yet been able to establish itself for vascular surgery. However, the preconditions for robot-assisted vascular interventions have changed fundamentally over the past years because of technological advances and extensive experience in other surgical disciplines. Hence, we describe a robot-assisted repair of an iliac artery aneurysm using a late-generation robotic platform. A 63-year-old male patient was diagnosed with an asymptomatic 30 mm aneurysm of the right common iliac artery. The operation was performed with the Da Vinci Xi system (Intuitive Surgical, Inc., Sunnyvale, CA, USA) using a direct transperitoneal approach to repair the aneurysm by interposition of a Dacron vascular prothesis. The total operating duration was 304 minutes without perioperative need for blood transfusion. The patient was discharged on the eighth postoperative day after an uneventful postoperative course. The case presented shows that robot-assisted surgery in the iliac axis can be performed safely with reasonable operating times.